Effects of EPHX1 and CYP3A4 polymorphisms on carbamazepine metabolism in epileptic patients - Caruso A; Bellia C; Pivetti A; Agnello L; Bazza F; Scazzone C; Bivona G; Lo Sasso B; Ciaccio M (Dove Medical Press, 2014)
Antonietta Caruso, Chiara Bellia, Alessia Pivetti, Luisa Agnello, Federica Bazza, Concetta Scazzone, Giulia Bivona, Bruna Lo Sasso, Marcello CiaccioDepartment of Biopathology and Medical and Forensic Biotechnologies, University of Palermo, Palermo, ItalyBackground: The aim of this study was to investigate the effect of two genetic polymorphisms in the coding regions (exon 3 and exon 4) of the EPHX1 gene, ie, 337T>C and 416A>G, respectively, on the metabolism of carbamazepine (CBZ) 10,11-epoxide (the active metabolite of CBZ) by evaluating the variation in serum CBZ 10,11-epoxide levels 4 hours after administration of the drug. Moreover, we reported the genotype frequencies of the CYP3A4*22 (rs 35599367, C>T) variant and its influence on the metabolism of CBZ.Methods: The analysis was performed in 50 patients receiving CBZ as monotherapy. DNA was extracted from leukocytes using a commercially available kit. Serum CBZ 10,11-epoxide levels were measured by high-performance liquid chromatography. Allelic discrimination was performed using polymerase chain reaction-restriction fragment length polymorphism. Statistical analysis of the difference in mean values for CBZ 10,11-epoxide levels according to genotype was performed using the Student's t-test with Statistical Package for the Social Sciences version 13 software.Results: Fourteen percent of the study group were CC, 42% were CT, and 44% were TT for the EPHX1 337T>C variant. No GG homozygote was identified for the EPHX1 416A.G variant; 64% were AA and 36% were AG. When we compared serum CBZ 10,11-epoxide levels 4 hours after drug administration, we found no statistically significant difference between the 337 CC, CT, and TT genotypes. Similarly, no difference in serum CBZ 10,11-epoxide levels was found between 416A>G AA and AG. Genotype frequencies for the CYP3A4*22 (rs 35599367 C>T) allelic variant were 94% for CC and 6% for CT, with no statistically significant difference in serum CBZ 10,11-epoxide levels between these genotypes 4 hours after administration of the drug (2.6±1.3 µg/µL and 2.5±1.2 µg/µL, respectively).Conclusion: Although there is some evidence of involvement of these polymorphisms in enzyme activity in vitro, we found no interference with CBZ metabolism in vivo.Keywords: EPHX1 gene, CBZ 10,11-epoxide, CYP3A4*22, drug metabolism